Research progress of humanistic care in nursing teaching and teacher training (人文关怀在护理教学与师资培养中的应用研究进展) - LI Yuxin (李玉欣); LI Xiuli (李秀丽); DENG Jianhua (邓建华); LIU Sichun (刘司春); TANG Ling (唐玲) (Association of Integrative Nursing, 2024)
Humanistic care ability is the guarantee for improving the quality of care and promoting patients' health. The aim of nursing teaching is not only to ensure that nursing students can acquire professional knowledge and practical skills, but also to establish a correct outlook on life, values, and good medical ethics, moreover, simultaneously addressing issues such as the disconnect between theory and practice and improving the effectiveness of clinical teaching. In addition, it is required to strengthen the training of nursing teachers to achieve a high level of consistency among clinical nurses and achieve the goal of mutual learning and teaching. This paper summarized the development of humanistic care in nursing teaching and the research progress of nursing teacher training, and provided reference for clinical practice and development of nursing industry. (人文关怀能力是提升护理质量、促进患者健康的保障。护理教学中不仅需要确保护理实习生掌握护理专业知识及技能, 而且还要帮助护理实习生树立正确的人生观、价值观以及良好的医德医风, 同时解决学生理论与实践脱节等问题, 提高临床教学效果。此外, 应加强对护理师资的培训, 使临床护士达到高水平的一致性, 达到教学相长的目的。本文探讨人文关怀在护理教学开展与护理师资培养中应用的研究进展, 为临床提供借鉴和参考, 推动护理事业的发展。)